Fiscal Decentralization and Regional Economic Growth: The Contrasting Effects of PAD and DAK in Gowa Regency, South Sulawesi - Tajuddin, Imran; Kessi, Andi Muhammad Fara (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study investigates the influence of Regional Own-Source Revenue (PAD) and the Special Allocation Fund (DAK) on regional economic growth within the framework of fiscal decentralization in Gowa Regency, South Sulawesi. The research aims to assess whether locally generated revenues and central government transfers effectively contribute to regional development and how fiscal autonomy interacts with transfer dependency in shaping economic outcomes. Using a quantitative approach, the study analyzes secondary data obtained from the Regional Financial Management Agency and the Central Bureau of Statistics for the period 2014–2023. The data were processed through multiple regression analysis to evaluate both individual and simultaneous effects of PAD and DAK on economic growth, measured by the Gross Regional Domestic Product at constant prices. The empirical findings reveal that both PAD and DAK significantly affect economic growth but in contrasting directions. PAD shows a significant positive effect, confirming that higher local revenue mobilization enhances fiscal independence and stimulates productive spending, thereby driving regional output. Conversely, DAK exhibits a significant negative impact, suggesting that dependence on central transfers can weaken local efficiency and create fiscal illusion, where spending increases without corresponding gains in productivity. The model’s moderate explanatory power indicates that while fiscal variables play a measurable role, other structural factors such as investment, human capital, and governance quality remain critical drivers of long-term growth. These results align with the theoretical perspectives of Fiscal Federalism, Fiscal Illusion Theory, and Public Choice Theory, highlighting the dual nature of decentralization—empowering yet potentially constraining when institutional capacity is weak. The study concludes that fiscal decentralization can effectively promote regional economic growth only when accompanied by strong local revenue capacity, transparent governance, and strategic use of transfers. Enhancing fiscal independence, reforming intergovernmental transfer mechanisms, and aligning fiscal policies with productive sectors are essential to realizing the developmental potential of decentralization. The findings provide practical insights for policymakers to strengthen fiscal resilience and ensure that decentralization supports inclusive and sustainable regional growth.